The effect of Centella asiatica L. Urban. and Curcuma longa L. extracts combination in improving memory performance in stroke model rats and its acute toxicity - Gofir, Abdul; Ar Rochmah, Mawaddah; Wibowo, Samekto; Hakimi, Mohammad; Mustofa (Indonesian Journal of Pharmacology and Therapy, 2021)
Post-stroke cognitive impairment involves memory, visuoconstructional, and spatial dysfunctions. Centella asiatica L. Urban. and Curcuma longa L. are both well-known herbs in South and South-East Asia countries that are believed to possess neuroprotective properties as memory enhancers. This study aimed to investigate the effects of C. asiatica L. Urban. and C. longa L. extracts combination in improving memory performance in stroke model rats and its acute toxicity. Twenty-five Wistar rats underwent transient bilateral common carotid artery occlusion. Y-maze pre-test was performed 24 h after the occlusion. The rats were then divided into five groups i.e. Group 1 received NaCMC dilution, Group 2 received donepezil 0. 7 mg/kg BW/day, and Groups 3, 4, and 5 received the extracts combination with dose of 59; 118; and 236 mg/kg BW/day, respectively. Y-maze post-test was performed 24 h after the last dose had been given. Spontaneous alternation behavior was used as the indicator of working memory measurement. The fixed-dose method according to OECD Guideline was used to estimate the LD50 in acute toxicity testing on Wistar rats. There was a significant difference in the delta spontaneous alternation percentage among groups tested (p<0. 05). Group 1 had significant difference with any other group (compared to Groups 2 to 5; p<0.05). No significant difference could be found between groups of the extracts combination and donepezil group suggesting that the effect is not more inferior nor dose-dependent in improving memory performance. The extracts combination at a single dose of 2000 mg/kg BW did not show related signs of toxicity or mortality in any of the rats during the 14-day observation period. In conclusion, the C. asiatica L. Urban. and C. longa L. extracts combination can improve performance of memory on stroke model animal. According to Globally Harmonized Classification System, the extracts combination can be classified as Category 5/unclassified.